Pengaruh Kewajiban Moral, Love of Money, Biaya Kepatuhan Pajak, dan Implementasi E-Samsat Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus Pada Kantor Bersama Samsat Kabupaten Buleleng) - Novi Purwanti; Nyoman Trisna Herawati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This study aims to determine the effect of moral obligations, love of money, the cost of tax compliance, and the implementation of e-Samsat on tax compliance. This study uses a quantitative approach, in which this study uses instruments in their measurements and processes them statistically. This research was conducted at the Samsat Office of the Regency of Buleleng. The population in this study are motor vehicle taxpayers registered with the Samsat Office in Buleleng Regency. The sampling method used in this study is a convenience sampling method using the Slovin formula, so that a sample of 100 respondents is obtained. The data of this study were collected using a questionnaire which was then processed by the multiple linear regression analysis test with the help of SPSS version 22. The results of the study stated that moral obligations and the implementation of e-Samsat have a positive and significant effect on motor vehicle taxpayer compliance, while love of money and tax compliance costs have a negative and significant effect on motor vehicle taxpayer compliance